Validation of the numerical model of a spark channel expansion in a low-energy atmospheric pressure discharge - Korytchenko, K.V.; Markov, V.S.; Polyakov, I.V.; Slepuzhnikov, E.D.; Meleshchenko, R.G. (Вопросы атомной науки и техники, 2018)
Gas-dynamic expansion of a low-energy atmospheric pressure spark discharge was numerically simulated. The
calculated data were compared with experimental results to validate the numerical model. A satisfactory correlation
of spark photo images with a simulated spark channel expansion was observed. It was found out that an experimental
total light intensity of spark discharge corresponds with spark radiation power. Time histories of a particle number
concentration and energy input were calculated. Radial temperature, pressure, density and conductivity profiles at
various times were investigated Чисельно досліджено газодинамічне розширення низькоенергетичного іскрового розряду атмосферного
тиску. Перевірка математичної моделі проведена шляхом порівняння чисельних та експериментальних результатів. Отримана задовільна кореляція фотозображень іскрового розряду з розрахунковими даними з розширення іскрового каналу. З’ясовано, що повна інтенсивність випромінювання іскрового розряду, яка
отримана експериментально, відповідає потужності випромінювання іскри. Розраховано розподіл концентрації компонентів та динаміка вводу енергії в іскру. Досліджені розподіли температури, тиску, густини та
провідності в радіальному розрізі в різні моменти часу. Численно исследовано газодинамическое расширение низкоэнергетического искрового разряда атмосферного давления. Проверка математической модели проведена путем сравнения численных и экспериментальных результатов. Получена удовлетворительная корреляция фотоизображений искрового разряда с расчетными данными по расширению искрового канала. Выявлено, что полная интенсивность излучения искрового разряда, получаемая экспериментально, соответствует мощности излучения искры. Рассчитано распределение концентрации компонентов и динамика ввода энергии в искру. Исследованы распределения температуры, давления, плотности и проводимости в радиальном сечении в разные моменты времени.